Automotive safety handbook - Seiffert, Ulrich, 1941- (SAE International, 2007)
Examining the state-of-the-art in passenger car vehicle safety, the book features thorough discussion of the interrelationships among the occupant, the vehicle, and the restraint system (in frontal, lateral, and rear impacts and rollover).
Keywords: Automobiles -- Safety appliances -- Handbooks, manuals, etc.; Automobiles -- Testing -- Handbooks, manuals, etc.; elektronické knihy; electronic books